TLC-densitometric analysis of allantoin in Symphytum officinale L. roots - Kimel Katarzyna; Zienkiewicz Magdalena; Sparzak-Stefanowska Barbara; Krauze-Baranowska Mirosława (Acta Pharmaceutica)
A TLC-densitometric method for determination of allantoin in Symphytum officinale root was developed. Densitometric quantification of allantoin was carried out on TLC Si60 plates with butanol-50 % methanol/formic acid, 66.5:33.2:0.3 (V/V/V) as developing solvent, at a wavelength of 190 nm. The method was preliminarily validated in terms of specificity, linearity, precision, limit of detection, limit of quantification, recovery and robustness. The results of TLC quantification were compared with HPLC analysis carried out on a HILIC Luna NH2 100A column, with mobile phase consisting of acetonitrile/water 80:20 (V/V) and UV detection at 190 and 210 nm. Allantoin content was determined in two herbal products and it varied from 0.94 to 2.09 %, depending on the producer, and was in agreement with literature reports.